Prognosis of Childhood Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
A cohort of 453 children, aged 1 month to 15 years, with newly diagnosed epilepsy was studied prospectively for 5 years at the Erasmus MC/Sophia Children's Hospital, Rotterdam and three other hospitals in the Netherlands, and the data analyzed to determine the prognosis, course, and response to treatment.